Regulation of MMP9 transcription by ETS1 in immortalized salivary gland epithelial cells of patients with salivary hypofunction and primary Sjögren’s syndrome - Braxton Noll; Farah Bahrani Mougeot; Michael T. Brennan; Jean-Luc C. Mougeot (Scientific Reports, 2022)
Abstract Primary Sjögren’s syndrome (pSS) patients exhibit enhanced degradation of the salivary epithelium initially through MMP9 overexpression. We assessed the expression of MMP9 and an associated transcription factor, ETS1, in primary salivary gland epithelial cells (SGECs) and investigated potential regulatory mechanism(s) in immortalized SGECs. SGECs and iSGECs were derived from pSS and/or xerostomic “sicca” patients. siRNA knockdown of ETS1 in iSGECs was performed to determine MMP9 mRNA (qRT-PCR) and protein expression (ELISA). ETS1 binding to MMP9 promoter was assessed by luciferase activity and binding confirmed by mutagenesis and ChIP. Effects of ETS1 overexpression on progenitor and Epithelial-Mesenchymal transition (EMT) associated markers were determined by Western blot. Expression of ETS1 and its phosphorylated form in iSGECs was determined by immunofluorescence microscopy. ETS1 and MMP9 were overexpressed in SGECs of pSS and non-pSS sicca patients with salivary gland lymphocytic infiltration compared to non-pSS sicca patients without infiltration. ETS1 siRNA knockdown reduced both MMP9 mRNA and protein levels. ETS1 overexpression affected the expression of EMT and progenitor cell markers. Lastly, ETS1 bound the MMP9 promoter within the DNA region of −296 bp to −339 bp. ETS1 may impair salivary function through direct transcriptional control of the MMP9 promoter. ETS1 upregulation may also affect other factors involved in repair of the dysfunctional pSS salivary epithelium.